2013
DOI: 10.1002/14651858.cd009453.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Mass media interventions for reducing mental health-related stigma

Abstract: The primary objective is to assess the effects of mass media interventions on reducing stigma related to mental health in terms of discrimination and prejudice compared to inactive controls. The secondary objective is to make comparisons of effectiveness based on the nature of the intervention, the type of the intervention, and the type of media.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
168
0
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 210 publications
(191 citation statements)
references
References 187 publications
4
168
0
7
Order By: Relevance
“…This finding is in line with a recent cross-sectional study carried out in Spain [50], with a similar methodology to those adopted in our study. It also confirms the positive impact that social media can have in challenging stigma attached to mental disorders [7] and supports the findings that at a population level it is possible to obtain a pattern of benefits for positive attitude changes [24]. It is interesting as in an omnibus survey carried out in the general population in England, a different pattern of change in attitudes was found [39], confirming that some contextual events -such as mass media coverage and reporting on mental health issues -can have an impact on attitudes toward mental illness [30,54].…”
Section: Discussionsupporting
confidence: 57%
“…This finding is in line with a recent cross-sectional study carried out in Spain [50], with a similar methodology to those adopted in our study. It also confirms the positive impact that social media can have in challenging stigma attached to mental disorders [7] and supports the findings that at a population level it is possible to obtain a pattern of benefits for positive attitude changes [24]. It is interesting as in an omnibus survey carried out in the general population in England, a different pattern of change in attitudes was found [39], confirming that some contextual events -such as mass media coverage and reporting on mental health issues -can have an impact on attitudes toward mental illness [30,54].…”
Section: Discussionsupporting
confidence: 57%
“…Previous work on mass media interventions aimed at reducing stigma have focused on changes in knowledge, attitudes and behaviour intentions of discrimination using survey measures. 6,8 Systematic reviews have reported that anti-stigma interventions were effective in changing attitudes. In addition, intervention groups experienced a decrease in prejudice outcomes compared with control groups immediately and months after the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, intervention groups experienced a decrease in prejudice outcomes compared with control groups immediately and months after the intervention. 6,8 However, discrimination outcomes were mixed. Effects ranged from an increase to a decrease or to no difference in effect, which may have been a result of heterogeneity in study design.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations